Predictive factors of long-term results following valve repair in ischemic mitral valve prolapse. (1st February 2016) - Nappi, Francesco; Nenna, Antonio; Spadaccio, Cristiano; Lusini, Mario; Chello, Massimo; Fraldi, Massimiliano; Acar, Christophe
Abstract: Background: In patients with ischemic mitral regurgitation, leaflet prolapse requires an accurate evaluation since surgical approach depends on valvular and subvalvular characteristics. This study aims to describe a cohort of patients over a long-term follow up, analyzing survival, reoperation and predictive factors of surgical outcomes. Methods and results: From March 1994 to June 2011, 75 patients with ischemic mitral regurgitation and leaflet prolapse underwent surgical myocardial revascularization and mitral valve repair (90.7%) or replacement (9.3%). Our cohort was followed up until April 2015, with a mean follow up of 7 ± 3 years. Cardiac-related deaths occurred in 26 patients, with a mean survival of 114.2 months, including eight patients with in-hospital mortality. Reoperation was performed in 14 patients, due to valve repair failure. Twenty-six patients experienced moderate-to-severe mitral regurgitation. A preoperative LVEDD > 62 mm, LVESD > 52 mm, previous anteroseptal myocardial infarction, diffuse coronary artery disease, papillary anatomy type 1, partial rupture of the papillary muscle, A1-A2 scallop prolapse and postoperative mitral valve configuration (tenting area, tenting height, alfa-1 angle and alfa-2 angle) were identified as independent predictors of poor outcome. An index quantifying the stress on the annulus imparted by annuloplasty was elaborated and predicted endpoints. Conclusion: Leaflet prolapse is an important entity in patients with ischemic mitral regurgitation, and its pathogenic mechanism mostly relies on papillary muscle lesion or elongation. Perioperative parameters describing geometric features of left ventricle, valvular and subvalvular components should be considered to provide a tailored approach for mitral valve repair, or to opt for immediate replacement in case of unfavorable geometry.